Osmotic dehydration of green mango samples (Mangifera indica L., Filipino var.) in ternary solutions - Ayala-Aponte, Alfredo A.; Molina-Cortés, Andrea; Serna-Cock, Liliana (Vitae, 2018)
Background: in Colombia the consumption of fresh green mango (also known as mango “biche”) is quite popular, and is consumed with lemon juice, salt, and honey. However, its high humidity content and high water activity makes of mango a highly perishable fruit, thus requiring processing alternatives. Osmotic dehydration (OD) is an interesting alternative for the conservation of mango. In OD, binary solutions (Solute + water) and ternary solutions (2 Solutes + water), have been traditionally used, however, more water removal can be achieved using ternary solutions, which leads to the improved organoleptic properties of dehydrated products. Objetives: to evaluate the kinetic water loss (WL), solutes gain (SG), weight reduction (WR), water activity (aw), and volume (Shrinking Coefficient, SC) in green mango (Mangifera indica L. Filipino variety) osmotically dehydrated (OD). Additionally, to calculate water and solutes diffusivity (Def ) for each treatment. Methods: green mango samples, with maturity scale zero, were used. Ternary solutions of sucrose at 40% and NaCl at 3, 6 and 9% were used for OD. The binary solution of sucrose with water as control treatment, was used. In the osmotic process samples were taken out at different times of OD (15, 30, 60, 90, 180, 240, and 300 min). Results: the findings show that at a higher concentration of NaCl, the dehydration kinetics was more rapid, aw and SC were smaller and water and solutes Def were higher. The samples dehydrated with the greatest solutes concentration (40-9%) reached the highest WL, SG, and WR with 89.52, 13.10, and 46.68%, respectively. Coefficients Defw and Defs showed a magnitude order of 10-10 m2/s, which is within the interval of dehydrated foods. Conclusions: this research showed that binary (sucrose + water) and ternary (NaCl + sucrose + water) solutions, are suitable for dehydrating green mango, however, the ternary solutions were more effective.